2016
DOI: 10.1038/aps.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

Bibenzyl compound 20c protects against endoplasmic reticulum stress in tunicamycin-treated PC12 cells in vitro

Abstract: Aim: Accumulation of α-synuclein (α-syn) in the brain is a characteristic of Parkinson's disease (PD). In this study, we investigated whether treatment with tunicamycin, an endoplasmic reticulum (ER) stress inducer, led to the accumulation of α-syn in PC12 cells, and where α-syn protein was accumulated, and finally, whether bibenzyl compound 20c, a novel compound isolated from Gastrodia elata (Tian ma), could alleviate the accumulation of α-syn and ER stress activation in tunicamycin-treated PC12 cells. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The elevation of IL-6 and phosphorylation of αSyn in 8-M-old seipin -nKO mice were sensitive to the GSK3β inhibitor and the PPARγ agonist, but it remains unclear whether αSyn phosphorylation is consequence of inflammation. On the other hand, ER stress is known to promote αSyn phosphorylation 30 . The αSyn phosphorylation can induce the activation of ER stress 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of IL-6 and phosphorylation of αSyn in 8-M-old seipin -nKO mice were sensitive to the GSK3β inhibitor and the PPARγ agonist, but it remains unclear whether αSyn phosphorylation is consequence of inflammation. On the other hand, ER stress is known to promote αSyn phosphorylation 30 . The αSyn phosphorylation can induce the activation of ER stress 31 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the levels of p-eIF2α and ATF4 were significantly decreased. Moreover, 20C reduced the accumulation of α-syn within cells concurrently, which further improved the cell viability [304]. In a separate experiment, it was found that 20C attenuated apoptosis and oxidative stress in rotenone-treated PC12 cells via activation of the nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant responsive element (ARE)/heme oxygenase-1 (HO-1) signaling pathway, which is strictly correlated with the PERK-mediated branch of the UPR signaling pathway [305].…”
Section: Gastrodia Elata Derivativesmentioning
confidence: 94%
“…In neuroprotection, scientists featured the bibenzyl compound, 20C, isolated from orchid Gastrodia elata Blume. It is also reported for oxidative stress-ameliorating efficacy against tunicamycin induced damage in endoplasmic reticulum and rotenone-triggered apoptosis [132,133]. The rotenone-induced neurotoxicity and Parkinson's disease (PD) development involves reduction of nuclear factor erythroid 2-related factor (Nrf2)-mediated antioxidant enzyme activity as well as DJ-1 level.…”
Section: Therapeutic Application Of Bibenzyls and Its Derivatives Exmentioning
confidence: 99%